Keeping it Real: Using Mechanisms to Promote Use in the Realist Evaluation of the Building Capacity to Use Research Evidence Program. Issue 167 (6th October 2020) - Punton, Melanie; Vogel, Isabel
Abstract: This chapter explores the use of mechanisms within the realist evaluation of the Building Capacity to Use Research Evidence (BCURE) program, a £15.7 million initiative aiming to improve the use of evidence in decision‐making in low and middle‐income countries. The evaluation was commissioned to establish not just whether BCURE worked but also how and why capacity building can contribute to increased use of evidence in policymaking in the very different contexts in which the program operated. This chapter argues that using mechanisms helped provide nuanced and robust insights into these questions, while also strengthening the usefulness and policy relevance of the evaluation. Drawing primarily on qualitative data, including interviews with more than 500 stakeholders over 3 years, the evaluation explored the mechanisms that promote capacities to use evidence in decision‐making, through developing and testing realist context‐intervention‐mechanism‐outcome configurations (CIMOs). Uncovering the value of mechanisms for policy and program learning was not easy, and the chapter sets out some of the thorny challenges faced and how the BCURE evaluation navigated these. Ultimately, the use of mechanisms in the BCURE evaluation helped to generate practical and nuanced insights that fed directly into the design of a £17 million follow‐up program. The seven mechanisms uncovered are continuing to inform our own and others' work on institutional capacity change in a wide range of fields.